PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA DINAS PERHUBUNGAN KABUPATEN SRAGEN - Windiatmoko, Gentur; Wahyudi, Amin; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims to determine the significant influence between (1) Job satisfaction on organizational commitment; (2) Work motivation towards organizational commitment; (3) Job satisfaction with OCB; (4) Work motivation towards OCB; (5) Organizational commitment to OCB; (6) Job satisfaction with OCB with organizational commitment as a mediating variable; (7) Work motivation towards OCB with organizational commitment as a mediating variable in the Transportation Agency of Sragen Regency. The population of the Sragen Regency Transportation Department employees is 94 people. Samples were taken by census sampling of 94 people. Data collection techniques using a questionnaire through the test of validity and reliability. The analysis technique uses multiple linear regression with the classic assumption test and the Sobel Test. Conclusion of research results; (1) Job satisfaction has a significant effect on organizational commitment. (2) Work motivation has a significant effect on organizational commitment. (3) Job satisfaction has a significant effect on OCB. (4) Work motivation has a significant effect on OCB. (5) Organizational commitment has a significant effect on OCB. (6) Organizational commitment mediates the effect of job satisfaction on OCB. (7) Organizational commitment mediates the effect of work motivation on OCB.